Additive and Laser Manufacturing for Multifunctional Electronics on High‐Performance Polymers - Joshua Vandervelde; Yeowon Yoon; Rifat Shahriar; Stephen B. Cronin; Yong Chen (Small Science)
Laser‐induced graphene (LIG) is a novel multifunctional material fabricated from a single‐step laser scribing process on a variety of polymers. LIG electronics display exceptional conducting, heating, and sensing properties, which are desirable for customizable circuits within 3D‐printed structures. However, the properties of LIG on high‐performance additive manufacturing (AM) materials, such as polyetherimide (PEI, trade name Ultem) and polyether ether ketone (PEEK), have not been thoroughly investigated. In this study, LIG is scribed by a blue laser on pure and 3D‐printed PEI and PEEK. Remarkably, the LIG's electrical performances represent several of the lowest sheet resistances reported on PEI‐ and PEEK‐derived LIG to date. These minimal values (1.02 Ω sq−1) and their high conductivities (45.4 S cm−1) are also among the best electrical characteristics studied on any LIG precursor. The versatility of LIG electronics for AM is further demonstrated on 3D‐printed specimens with laser‐scribed heaters and strain gauges. LIG heaters show impressive operating ranges and excellent electrothermal properties; LIG strain gauges exhibit large gauge factors and minimal drift. In these findings, an effective approach to fabricate facile electronics in AM structures by integrating additive and laser manufacturing processes is presented.